Pembangunan Ekonomi Masyarakat Berbasis Modal Sosial - Saifuddin, Saifuddin Endre (Universitas Brawijaya, Indonesia, 2008)
Definition of Social Capital among expert of Economics and expert of Social Science is different each other, however in general social capital has three main elements, those are: (1) Trust, (2) Norm and (3) Job network. The three elements can be used as an approach to measure the level of social capital in a region. Social capital can be differered into two dimensions; Structural and cognitive. Structural dimension see how process, quality and social interaction of society measured from its involvement in local association. Without social capital, active of economic development as well as construction will be difficult to realized. Social capital is not a single entity, but it is various entities which consist of some social structure aspects.